Alterations of gene expression indicating effects on estrogen signaling and lipid homeostasis in seabream hepatocytes exposed to extracts of seawater sampled from a coastal area of the central Adriatic Sea (Italy). (February 2017) - Cocci, Paolo; Capriotti, Martina; Mosconi, Gilberto; Campanelli, Alessandra; Frapiccini, Emanuela; Marini, Mauro; Caprioli, Giovanni; Sagratini, Gianni; Aretusi, Graziano; Palermo, Francesco Alessandro
Abstract: Recent evidences suggest that the toxicological effects of endocrine disrupting chemicals (EDCs) involve multiple nuclear receptor-mediated pathways, including estrogen receptor (ER) and peroxisome proliferator-activated receptor (PPAR) signaling systems. Thus, our objective in this study was to detect the summated endocrine effects of EDCs with metabolic activity in coastal waters of the central Adriatic Sea by means of a toxicogenomic approach using seabream hepatocytes. Gene expression patterns were also correlated with seawater levels of polychlorinated biphenyls (PCBs) and polycyclic aromatic hydrocarbons (PAHs). We found that seawater extracts taken at certain areas induced gene expression profiles of ERα/vitellogenin, PPARα/Stearoyl-CoA desaturase 1A, cytochrome P4501A (CYP1A) and metallothionein. These increased levels of biomarkers responses correlated with spatial distribution of PAHs/PCBs concentrations observed by chemical analysis in the different study areas. Collectively, our data give a snapshot of the presence of complex EDC mixtures that are able to perturb metabolic signaling in coastal marine waters. Highlights: ERα and VTG were induced by samples from transect I in two of the areas studied. Water samples taken at certain areas induced expression profiles of PPARα/SCD1A. Gene biomarkers were not modulated by exposure to samples from the reference site. Biomarkers responses correlated with spatial distribution of PAHs/PCBs levels. Data suggest EDCs contamination for the upstream and downstream river site samples.